Practices Associated with Serum Antiepileptic Drug Level Monitoring at a Pediatric Neurology Clinic: A Malaysian Experience - Salih, M. R. M.; Bahari, M. B.; Hassali, M. A. A.; Shafie, A. A.; Al-lela, Omer Qutaiba; Abd, A. Y.; Ganesan, V. (2013)
OBJECTIVES: To assess the practices associated with the application of therapeutic drug monitoring (TDM) for antiepileptic drugs (AEDs) in the management of children with structural-metabolic epilepsy.